Methodological Features of the Organization of Independent Work of Students in the Process of Teaching Mathematics - Ismanov Abdusalom (Research Parks Publishers, 2021)
The article deals with the features of the organization of independent work of students in mathematics, depending on the direction of specialization. The main types of independent work of students, the stages of its organization are indicated, examples of independent work of students of humanitarian and technical directions are given.